The Role of Monk Parakeets as Nest-Site Facilitators in Their Native and Invaded Areas - Dailos Hernández-Brito (Biology, 2021)
While most of the knowledge on invasive species focuses on their impacts, little is known about their potential positive effects on other species. Invasive ecosystem engineers can disrupt recipient environments; however, they may also facilitate access to novel resources for native species. The monk parakeet (Myiopsitta monachus) is a worldwide invader and the only parrot that builds its own communal nests, which can be used by other species. However, the ecological effects of these interspecific interactions are barely known. We compared the role of the monk parakeet as a nest-site facilitator in different rural and urban areas, both invaded and native, across three continents and eight breeding seasons. A total of 2690 nests from 42 tenant species, mostly cavity-nesting birds, were recorded in 26% of 2595 monk parakeet nests. Rural and invaded areas showed the highest abundance and richness of tenant species. Multispecies communal nests triggered interspecific aggression between the monk parakeet host and its tenants, but also a cooperative defense against predators. Despite the positive effects for native species, monk parakeets also facilitate nesting opportunities to other non-native species and may also transmit diseases to tenants, highlighting the complexity of biotic interactions in biological invasions.